The Effect of Buyer-supplier Partnership and Information Integration on Supply Chain Performance: An Experience from Chinese Manufacturing Industry - Shahzad Ahmad Khan; Yan Liang; Shahzad Sumaira (International Journal of Supply Chain Management, 2015)
Coordination, collaboration, and cooperation are often used in business term to enhance productivity and performance, in this way the partnership with supplier and information integration always play an important role in supply chain. This study investigates the effect of Buyer-supplier partnership and information integration on supply chain performance. The study also elaborates the development of trust and guanxi between suppliers and buyers for better business environment in supply chains. This study uses structural equation modeling to analyze data collected from 218 Chinese manufacturing industries. The Buyer-supplier relationship significantly affects trust and guanxi, which subsequently influences two elements of information integration, namely, quality information and real-time information. We found that Buyer-supplier partnership and information integration have a significant effect on supply performance. Furthermore, we found that trust and guanxi are pivotal role in sustaining better relationship between supplier and business for long run and growth